2022
DOI: 10.5811/westjem.2021.12.54010
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Escape Room versus Lecture on Infectious Disease Content: Effect on Resident Knowledge and Motivation

Abstract: Introduction: Medical educators are constantly seeking methods to increase engagement in the era of coronavirus disease 2019 (COVID-19) where virtual and blended learning formats are increasingly common. Educational escape rooms have previously been used to motivate learners, enhance communication skills, and cultivate teamwork. However, it is not known whether escape rooms increase learner knowledge as compared to a lecture format. Methods: This quasi-experimental study included 30 emergency medicine reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…There are a couple of studies that described their experience and adaptation of virtual interactive learning during COVID-19. Most of these studies found a similar perception of VERs to previously documented perceptions of live-escape rooms [ 17 , 18 , 19 , 20 , 21 , 22 ]. However, none of these virtual escape rooms covered pharmacotherapy courses.…”
Section: Introductionsupporting
confidence: 67%
“…There are a couple of studies that described their experience and adaptation of virtual interactive learning during COVID-19. Most of these studies found a similar perception of VERs to previously documented perceptions of live-escape rooms [ 17 , 18 , 19 , 20 , 21 , 22 ]. However, none of these virtual escape rooms covered pharmacotherapy courses.…”
Section: Introductionsupporting
confidence: 67%
“…La tabla 4 demuestra que a los estudiantes que les gusta jugar, despiertan su imaginación al estar realizando esta actividad, estos datos coinciden con otras investigaciones previas en las que los participantes disfrutan de los Escape Room encontrándoles interesantes, interactivos, divertidos, motivadores para resolver retos mediante la atracción y así mejorar el aprendizaje de una forma eficaz al proporcionar conocimientos en comparación a una clase en formato tradicional (Dimeo et al, 2022).…”
Section: Fuente: Encuestaunclassified
“…Educational escape rooms have rapidly become popular within health professions' education [15]. A variety of studies have explored the capacity of escape rooms to facilitate learning in clinical [16][17][18][19][20] and professional skills [21][22][23] domains. Research, however, is at an early stage with relatively little known about how learning takes place within these novel environments [24].…”
Section: Introductionmentioning
confidence: 99%